2019
DOI: 10.1007/s12088-019-00786-1
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic Diversity in Oxygen Depleted Waters of the Bay of Bengal Inferred Using Culture-Dependent and -Independent Methods

Abstract: There are regions in the world oceans where oxygen saturation is at its lowest, evident at depths between shelf to upper bathyal zone. These regions are known as Oxygen Minimum Zones (OMZs), which reportedly support phylogenetically diverse microbes. In this study, we aimed to characterize prokaryotic diversity in the water samples collected from 43, 200 and 1000 m depth of the Bay of Bengal Time Series location (BoBTS-18.0027°N, 89.0174°E) in the OMZ region. Illumina sequencing generated 3,921,854 reads of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
5
13
1
Order By: Relevance
“…Recently, similar to the present study in the BoBTS, V3 hyper-variable region of 16S rRNA genes was sequenced (97% sequence similarity), reported high diversity at the core and lower OMZ than the surface. Due to restricted sampled depths and higher DO concentration within the core OMZ (1.5 µM) than the present study (0.6 µM) (Fernandes et al, 2019), this could be a reason for such divergent findings. Bryant et al (2012) speculated lower redox potentials and less readily available organic matter conditions in the core OMZ of ETSP to be one of the reasons of low energy availability and thus the cause of reduced microbial richness.…”
Section: Alpha Diversity Of Bacterial Communitiescontrasting
confidence: 78%
See 3 more Smart Citations
“…Recently, similar to the present study in the BoBTS, V3 hyper-variable region of 16S rRNA genes was sequenced (97% sequence similarity), reported high diversity at the core and lower OMZ than the surface. Due to restricted sampled depths and higher DO concentration within the core OMZ (1.5 µM) than the present study (0.6 µM) (Fernandes et al, 2019), this could be a reason for such divergent findings. Bryant et al (2012) speculated lower redox potentials and less readily available organic matter conditions in the core OMZ of ETSP to be one of the reasons of low energy availability and thus the cause of reduced microbial richness.…”
Section: Alpha Diversity Of Bacterial Communitiescontrasting
confidence: 78%
“…It was observed that in the present study higher OTU richness could be recovered at ASTS with the use of high throughput sequencing. However, at BoBTS, higher OTU richness was reported in Fernandes et al (2019) where similar molecular identification method was employed. Notably, the DO concentration observed during Fernandes et al (2019) study was higher than those observed in BoBTS-OMZ in the present study.…”
Section: Alpha Diversity Of Bacterial Communitiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Large amounts of particulate and dissolved organic matter are characteristic of the watercourses flowing into the Bay of Bengal. Gammaproteobacteria and Alphaproteobacteria dominated the bacterial community composition of the waters of the Bay of Bengal (Ghosh and Bhadury, 2018;Rajpathak et al, 2018;Fernandes et al, 2019;Dhal et al, 2020) and these classes together with Deltaproteobacteria were detected abundantly in sediments of the Sundarbans (Basak et al, 2015). In this study, Deltaproteobacteria were mainly represented by Geobacter at K8 with relevance for the arsenic cycle (Gnanaprakasam et al, 2017).…”
Section: Bacterial Community Composition and Potential Roles Across Tmentioning
confidence: 49%